Customer Orientation and Financial Performance: Women in Top Management Teams Matter! - Srivastava, Chandra; Kashmiri, Saim; Mahajan, Vijay (Journal of Marketing, 2023)
Using a longitudinal analysis of publicly traded Fortune 500 firms, the authors find support for their hypotheses that a relative increase in female influence in the top management team (FITMT) is positively associated with (1) customer orientation of the firm and (2) long-term financial performance (i.e., Tobin's q). They demonstrate that customer orientation partially mediates the relationship between FITMT and long-term financial performance. The authors also explore environmental and corporate governance factors that moderate the link between FITMT and customer orientation. They find that this link is attenuated for firms that operate under high environmental dynamism and low environmental discretion, and for firms with high family ownership. Having high female representation among board members and more marketing-experienced board members strengthens the link between FITMT and customer orientation. These findings have important implications for scholars, boards, chief executive officers, and investors interested in identifying environmental and corporate governance factors that facilitate a greater focus on customers at the highest levels of the firm.